2006
DOI: 10.1111/j.1440-1630.2006.00591.x
|View full text |Cite
|
Sign up to set email alerts
|

Framing a set of non‐academic selection criteria for occupational therapy students: An Australian study

Abstract: Background/Aim: Demand for places in occupational therapy programs at Australian universities may place undue emphasis on academic attainment when selecting students … but how else might students be selected? This study investigated those attributes judged by occupational therapy practitioners to be most important. Methods: From a focus group of occupational therapy academics, a list of occupational therapy practice attributes was generated and used to develop a questionnaire completed by 175 Australian occupa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…With regard to non-cognitive admission factors, the results of both the survey (67%, n=30) and website review (52%, n=172) showed that the majority of programs use interviews as part of the admission process, despite the paucity of evidence to support the predictive value of an interview. Interviews are often cited as a means to measure non-cognitive variables, but this has not been supported through empirical data with allied health professions (Grapczynski & Beasley, 2013;Lyons et al, 2006). The prevalence of interviews and other non-cognitive factors within the admission process may demonstrate programs' desire to consider a more holistic view of a prospective student than P-GPA or GRE scores can provide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to non-cognitive admission factors, the results of both the survey (67%, n=30) and website review (52%, n=172) showed that the majority of programs use interviews as part of the admission process, despite the paucity of evidence to support the predictive value of an interview. Interviews are often cited as a means to measure non-cognitive variables, but this has not been supported through empirical data with allied health professions (Grapczynski & Beasley, 2013;Lyons et al, 2006). The prevalence of interviews and other non-cognitive factors within the admission process may demonstrate programs' desire to consider a more holistic view of a prospective student than P-GPA or GRE scores can provide.…”
Section: Discussionmentioning
confidence: 99%
“…Dahlin, Söderberg, Holm, Nilsson, and Farnebo (2012) found interviews to have minimal predictive value in identifying medical students at risk of poor communication skills, but failed to identify students' capacity for success in academic or clinical performance. Despite the evidence, interviews often have been cited as a method to measure non-cognitive variables, such as communication and interpersonal skills, in health professions literature (Dahlin et al, 2012;Eva, Rosenfeld, Reiter, & Norman, 2004;Goho & Blackman, 2006;Lyons, Mackenzie, Bore, & Powis, 2006).…”
Section: Non-cognitive Admission Factorsmentioning
confidence: 99%
“…Critical thinking or parts of it, was generally ranked well by other researchers. A study by Lyons looking at non‐academic selection criteria for occupational therapy students ranked ‘problem‐solving skills’ as the second most important ‘element’ and the theme of ‘problem‐solving/critical thinking’ was deemed to be significant (Lyons et al ., ). Orlick () reported the ability to ‘use feedback and to act on lessons learned’ as important for personal excellence and Lambe and Bristow () similarly placed the ‘ability to cope with ambiguity, complexity and uncertainty’ as the sixth most important attribute (out of a possible 20) required for good doctors.…”
Section: Discussion: Attributes Of Excellencementioning
confidence: 97%
“…The importance of communication is supported by most of the authors who studied variations of ‘excellence’ in different professions. The results of Lyons’ study looking at non‐academic selection criteria for occupational therapy students, rated verbal communication skills as the most important (Lyons, Mackenzie, Bore & Powis, ). Similarly, Lambe and Bristow's () study looking at the attributes of good doctors ranked verbal communication third in importance, and Smith et al .…”
Section: Discussion: Attributes Of Excellencementioning
confidence: 99%
“…This instrument has been used to assess the noncognitive traits of applicants in medicine, occupational therapy, social work, and other areas (Gibbons, Bore, Munro, & Powis, 2007;James et al, 2009;Lumsden et al, 2005;Lyons, Mackenzie, Bore, & Powis, 2006;. It has been shown to have good reliability and construct validity in studies involving medical school applicants, medical students, and psychology students in Australia, Israel, Fiji, New Zealand, Scotland, and England (Bore et al, 2005a;Bore, Munro, Kerridge, & Powis, 2005b;Munro et al, 2005).…”
Section: Introductionmentioning
confidence: 97%